Comparative analysis of internal auditing in Lithuania and Poland - Lakis, Vaclovas (Publishing House of the Wrocław University of Economics, 2009)
In today’s global world, where the free movement of capital, labour force and goods is possible, it is very important to have the most detailed information about the law regulating the performance of governmental institutions and private companies in different countries, how accountancy is managed, financial statements are produced, internal control in institutions and enterprises is secured. It is very important for the countries which closely cooperate politically and economically, e.g. Lithuania and Poland which have been very close in political, economic and cultural sectors for many years. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 278-286